METODE TERJEMAHAN ISTILAH ASING DARI BAHASA INGGRIS KE BAHASA INDONESIA DALAM KAMUS BESAR BAHASA INDONESIA EDISI IV - Rachmawati, Dian Karina (Jurnal Pena Indonesia, 2017)
Foreign terms from English into Indonesian in Indonesian dictionary the fourth edition is analyzed based on morphophonemic. Morphophonemic based translation process is based on the form (Form-based translation) and translation based on meaning (Meaning-based translation) (Larson, 1984). The shape of these foreign terms will be analyzed using the theory of generative phonology transformation (Schane, 1992) which is based on the change in morpheme formation of foreign terms to find the meaning of the translation process either BSu or the meaning of the grammatical BSa. This study uses a tool agih determining precisely which part of the language in question (Sudaryanto, 1993:15). This research method has three techniques, namely (1) elicitation, (2) a large library Indonesian Dictionary Fourth Edition (2012) and English dictionary, and (3) the recording or transcription. The results of this study is the term foreign English into Indonesian spelling is undergoing a process of adjustment in accordance with the rules of phonotactics in Indonesian so that it can pass through several stages to thank the suffixes are morphophonemic adjustments and not be separated from the shift in the meaning of BSU to BSA so that the reader the foreign term to understand the intended meaning of the presence of foreign terms.